Carbimazole-induced eosinophilic gastroenteritis in a young female with abdominal pain and ascites: a case report - Khadija Hafidh; Touseef Kazmi; Abeer Alhaj; Zufana Nazir (Journal of Medical Case Reports)
Abstract Background Eosinophilic gastroenteritis is a rare disease characterized by eosinophilic infiltration into one or more layers of the gastrointestinal tract. It commonly affects children more than adults. The clinical features depend on the site of gut involvement, but the most common symptoms include abdominal pain and diarrhea. The most common cause reported in the literature is hypersensitivity, as many patients have a history of seasonal allergies, atopy, asthma, food allergies, and so on. However, drugs can be a rare triggering factor. In the literature review, we found multiple case reports of eosinophilic gastroenteritis; however, only one other case of carbimazole-induced eosinophilic gastritis has been reported. Case presentation We report herein the case of a 36-year-old female from the Philippines who developed eosinophilic gastroenteritis localized to the esophagus and ileum 12 months following treatment with carbimazole for hyperthyroidism. In our facility, she was extensively investigated for malignancy, autoimmune pathologies and infectious etiologies. As the symptoms coincided with carbimazole exposure and other causes were ruled out, we labeled her as carbimazole-induced eosinophilic gastroenteritis. On subsequent follow-up after discharge, her symptoms and eosinophilia resolved when carbimazole was discontinued, suggesting a causative role. This is the first case of eosinophilic gastroenteritis secondary to carbimazole encountered in our region. Conclusion Diagnosis of eosinophilic gastroenteritis requires three criteria, namely (1) presence of gastrointestinal symptoms, (2) histologic evidence of eosinophilic infiltration in one or more areas of the gastrointestinal tract, and (3) exclusion of other causes of tissue eosinophilia. Our patient fulfilled all the criteria; additionally, she had a positive history of atopic tendencies and drug exposure. The diagnosis of hyperthyroidism was established a year ago and in another facility, so we were not sure of the underlying etiology of hyperthyroidism. Upon subsequent follow-up, her thyroid function remained stable. The case highlights the need for a collaborative multidisciplinary approach toward managing rare conditions.